Comparison of Education Policy USA & Indonesia - Ulul Albab (Ridwan Institute, 2022)
In public policy, both from Feldman's and Heidenheimer's definitions of CPP (Comparative Public Policy), we can conclude that there are 3 elements (elements) that are keywords that are the center of attention of CPP. In Feldman's terms, the 3 keywords are